2019
DOI: 10.1155/2019/8043248
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Pore Characteristics and Fractal Dimension Calculation of Pore Structure of Aerated Concrete Block

Abstract: It is important to control and predict the macroscopic properties through pore structure parameters of cement-based materials. Microscopic pore structure of concrete has many characteristics, such as sizes and disordered distribution. It is necessary to use fractal theory to describe the pore structure of concrete. In order to establish the relationship between the pore structure characteristics of aerated concrete and porosity, shape factor, pore superficial area, average pore diameter, and average diameter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…A large number of researchers have shown that the pore structure of concrete has obvious fractal characteristics [44][45][46]. Fu and Yu [47] calculated the fractal dimension of the pore structure of aerated concrete blocks and found that there was a significant linear relationship between pore fractal dimension and pore structure characteristics. Based on the MIP method and the fractal model, Jin et al [43] obtained the relationship between the fractal dimension of the pore surface of cement mortar and the pore characteristic parameters, which is the same as the rule of this paper.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A large number of researchers have shown that the pore structure of concrete has obvious fractal characteristics [44][45][46]. Fu and Yu [47] calculated the fractal dimension of the pore structure of aerated concrete blocks and found that there was a significant linear relationship between pore fractal dimension and pore structure characteristics. Based on the MIP method and the fractal model, Jin et al [43] obtained the relationship between the fractal dimension of the pore surface of cement mortar and the pore characteristic parameters, which is the same as the rule of this paper.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Fu J. et al [37,38] obtained the permeability parameters by reconstructing the mesoscale two-dimensional and three-dimensional numerical models of the wall material, which provided a theoretical basis for the simulation of the wall seepage process and leakage prevention under various working conditions. The authors also independently designed a laboratory device for testing the permeability of manufactured aerated concrete blocks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, X-CT has been gradually applied to research in the field of building materials, such as cement hydration, characterization of pore structure, transition zone of mortar interface, geometric distribution of fibers in concrete, sulfate erosion, steel corrosion, carbonization, etc., [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Jun et al [ 32 ] used X-CT to research the relationships between pore structure fractal dimension and pore structure parameters and introduced the calculation method of fractal dimension according to MATLAB. Wang et al [ 33 ] studied the spatial distribution of steel fibers and bubbles in UHPC samples by X-CT technology.…”
Section: Introductionmentioning
confidence: 99%